Metastatic bone disease: fundamental and clinical aspects - Diel, Ingo J.; Kaufmann, Manfred; Bastert, Gunther (Springer Berlin Heidelberg, 1994)
"Metastatic Bone Disease: Fundamental and Clinical Aspects" is an expanded version of a workshop on bone metastases which was held in Heidelberg, Germany, in April 1993. Bone metastases very often develop from malignant tumors and lead to complications which considerably diminish the quality of life of the patient. Bone pain, pathological fractures, and hypercalcemic syndrome should be recognized and treated ear- ly, so as to prevent any further morbidity and immobilizati- on. Antiosteolytic substances such as biophosphonate can supplement the established palliative and supportive thera- pies. Highly qualified basic researchers and clinicians in pathophysiology, diagnosis, and treatment of metastatic bone disease have contributed to this book, providing a good overview ofpresent knowledge and research. The book will be of interest not only to specialists, but also to any physi- cian interested in oncology